2021
DOI: 10.1158/1055-9965.epi-20-0694
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tumor Mutation Burden Analysis in Detecting Lynch Syndrome in Precision Medicine: Analysis of 2,501 Japanese Cancer Patients

Abstract: Background: Tumor mutation burden (TMB) is the total exonic mutation count per megabase of tumor DNA. Recent advances in precision medicine occasionally detect Lynch syndrome (LS) by germline sequencing for mismatch-repair (g.MMR) genes but not using TMB. The current study analyzes the utility of TMB in detecting LS. Methods: Whole-exome sequencing (ion-semiconductor sequencing) was performed for somatic and germline DNA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…For pancreaticobiliary cancers, the higher indication of ICI was expected because of their aggressive biological behavior and poor prognosis but much improved in cases with MSI-H and treated by ICI [ 37 ]. However, the current cases, including 25 familial pancreatic cancers and 2 familial biliary cancers, showed a very low MSI-H incidence (0.6–1.6%), similar to the low level of tumor mutation burden (0.5–2.2/Mb) demonstrated in our previous study [ 34 ]. In pancreatic and ovarian cancers, PARP inhibitors are effective when the patients harbor germline variants in the genes associated with homologous recombination pathways.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…For pancreaticobiliary cancers, the higher indication of ICI was expected because of their aggressive biological behavior and poor prognosis but much improved in cases with MSI-H and treated by ICI [ 37 ]. However, the current cases, including 25 familial pancreatic cancers and 2 familial biliary cancers, showed a very low MSI-H incidence (0.6–1.6%), similar to the low level of tumor mutation burden (0.5–2.2/Mb) demonstrated in our previous study [ 34 ]. In pancreatic and ovarian cancers, PARP inhibitors are effective when the patients harbor germline variants in the genes associated with homologous recombination pathways.…”
Section: Discussionsupporting
confidence: 89%
“…Generally, MSI in LS-related cancers has been reported in lower frequencies in Asian countries; for example, 17.3–25.7% [ 26 28 ] in EC, 4.3–10.0% in CRC [ 26 , 29 31 ], and 2.3–9.3% in gastric cancer [ 26 , 29 , 32 ], suggesting an ethnic deviation. This is also reflected in the lower incidences of LS in Asian countries (2.9% [ 33 ]–4.4% [ 28 ] in EC and 0.6% [ 34 ]–0.7% [ 35 ] in CRC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunotherapy may have better control of hereditary CRC than other systematic strategies. 25,26 In contrast to genetic alterations at DNA level, transcriptional alterations, and expression alterations showed a large variety of observations with little consensus. For example, some studies identified the expression of single markers for prognosis prediction, such as CD133, 27 HSF4, 28 and PLAC1, 29 etc., while other studies identified panels of genes with significant efficacy in prognosis prediction at protein expression levels, mRNA levels or miRNA levels of multiple genes.…”
Section: The Cancer Tissue Transcriptional Change Was Capable Of Pred...mentioning
confidence: 99%